THE REASONS WHY JADIDISM STARTED IN TURKESTAN - Salohiddinov Bunyod (TADQIQOTLAR.UZ, 2023)
Abstract: The article provides information about the emergence of the Jadidist movement in Turkestan and its role in the development of education.